The Joint Research Centre-European Network of Cancer Registries Quality Check Software (JRC-ENCR QCS) - Giusti, Francesco; Martos, Carmen; Adriani, Stefano; Flego, Manuela; Carvalho, Raquel Negrão; Bettio, Manola; Ben, Enrico (Frontiers in Oncology, 2023)
The core activity of population-based cancer registries (PBCRs) is to gather information from all new cancer cases in a defined geographic area, in order to measure the magnitude of cancer burden and to provide a basis for cancer research. The Joint Research Centre-European Network of Cancer Registries Quality Check Software (JRC-ENCR QCS) is a Java standalone desktop application, under development since 2015, created to support PBCRs in the validation of the collected data. The JRC-ENCR QCS performs internal consistency checks on the cancer registry dataset, to detect impossible or unlikely codes or combination of codes, and is thereby an important tool to support the validation efforts by registries and improve data quality and European-wide harmonisation. The software package also includes the JRC CSV Data layout converter, a complementary tool for transforming PBCR incidence files into a format compatible with the JRC-ENCR QCS. This paper gives an overview of the JRC-ENCR QCS, describing the role of the software in processing data files submitted by PBCRs contributing to the European Cancer Information System (ECIS) as well as its functionalities. The development of the JRC-ENCR QCS is an evolving process, with regular updates implementing new and revised European and International recommendations and classifications.